Nuclear DNA replication and repair in parasites of the genus Leishmania: Exploiting differences to develop innovative therapeutic approaches. (4th March 2017) - Uzcanga, Graciela; Lara, Eliana; Gutiérrez, Fernanda; Beaty, Doyle; Beske, Timo; Teran, Rommy; Navarro, Juan-Carlos; Pasero, Philippe; Benítez, Washington; Poveda, Ana
Abstract: Leishmaniasis is a common tropical disease that affects mainly poor people in underdeveloped and developing countries. This largely neglected infection is caused by Leishmania spp, a parasite from the Trypanosomatidae family. This parasitic disease has different clinical manifestations, ranging from localized cutaneous to more harmful visceral forms. The main limitations of the current treatments are their high cost, toxicity, lack of specificity, and long duration. Efforts to improve treatments are necessary to deal with this infectious disease. Many approved drugs to combat diseases as diverse as cancer, bacterial, or viral infections take advantage of specific features of the causing agent or of the disease. Recent evidence indicates that the specific characteristics of the Trypanosomatidae replication and repair machineries could be used as possible targets for the development of new treatments. Here, we review in detail the molecular mechanisms of DNA replication and repair regulation in trypanosomatids of the genus Leishmania and the drugs that could be useful against this disease.